Sonographic Aspects of Splenic Torsion Due to Abdominal Eventration in a Dog - Salgueiro, Nathalia Brant Malta; Lacreta Junior, Antonio Carlos Cunha; Tavares, Ana Carolina Giudice; Santos, Mariana Avelino de Souza (Acta Scientiae Veterinariae, 2017)
Background: The splenic torsion is a rare condition in dogs, especially when it is not associated with gastric dilatation and volvulus. Abdominal ultrasonography has been reported as an accurate diagnostic method in cases of splenic torsion suspicions. Splenomegaly, decreased echogenicity of the parenchyma of the spleen and hypoechoic appearance or “lace” are suggestive sonographic findings, although the definitive diagnosis is given through exploratory laparotomy. This study reports a case of splenic torsion followed by abdominal trauma and eventration in a dog, highlighting the importance of the ultrasound examination. Case: An adult dog without a defined breed pattern that weighed 8.6 kg was referred to the Veterinary Hospital of the Federal University of Lavras (Universidade Federal de Lavras - UFLA) with a history of trauma caused by having been run over by a car 24 h earlier. The animal exhibited right inguinal region swelling with hematoma and a loss of local muscular tension. An abdominal ultrasound indicated that the spleen was displaced to the right inguinal region and that a portion of the spleen was included in the animal’s abdominal eventration. The spleen possessed an irregular surface with increased dimensions and diffusely decreased echogenicity and multiple parallel echogenic lines (in the reticular aspect). Abrupt differences in the echogenic textures of the spleen were identified in certain images. Color Doppler assessments revealed no blood flow. Based on the aforementioned ultrasound findings, an exploratory laparotomy was indicated. The laparotomy confirmed the presence of right inguinal abdominal muscle rupture with dislocation, eventration, and splenic torsion. Discussion: Splenic torsion may be most frequently reported in cases involving large and giant male dogs because this condition is typically related to dilatation syndrome and gastric volvulus, which are more prevalent among large and giant male dogs than among other dogs. Although these etiological factors should be considered, in the case examined in this study, the patient most likely suffered from splenic torsion caused by abdominal trauma, which resulted in the rupture of the gastrosplenic and splenocolic ligaments and the splenic vessels and thereby created circumstances conducive to splenic eventration and torsion. The sonographic features of splenic torsion in dogs include marked splenomegaly, a hypoechoic or diffuse anechogenic pattern that indicates the presence of vascular congestion, and sinusoidal dilatation separated by small linear echoes that represent dilated vessels. In cases of splenic torsion, two-dimensional ultrasonographic images may reveal an enlarged spleen with a hypoechoic echotexture and a hyperechoic triangle between the veins and the splenic parenchyma continuous to the hyperechoic mesentery. The sonographic findings observed in the patient examined in this study were similar to the findings described in the published literature and consistent with the results reported by the other authors. Although extensive literature reports have described the sonographic aspects of splenic torsion in dogs, this disease remains uncommon. Moreover, no prior reports have described splenic torsion secondary to concurrent abdominal trauma, displacement, and eventration; thus, the case examined in this study is unprecedented, and the ultrasonographic aspects observed in this case should be considered.